ERROR IN DETERMINING THE PERMANENT CORRECTION OF THE MEASURED DISTANCE BY A GROUND LASER SCANNER: ERROR IN DETERMINING THE PERMANENT CORRECTION OF THE MEASURED DISTANCE BY A GROUND LASER SCANNER - Yanchev, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The subject of the research is to make a correct assessment of the error in determining the constant correction of the measured distance and to choose a model for their removal, which will allow achieving the required accuracy and high productivity with minimal material costs when performing laser measurements.